MAFLD - a new approach to fatty liver disease - Łozowski, Borys; Brzuszkiewcz-Łozowska, Kinga; Kułaga, Monika; Kasprzak, Anna; Grzybek, Monika; Mazur-Lesińska, Diana; Szostak, Barbara; Wielgosz-Biała, Sylwia; Tyszkiewicz, Krzysztof; Wilczyńska, Barbara; et al. (Journal of Education, Health and Sport, 2025)
Fatty liver disease associated with metabolic dysfunction (MAFLD) is a term introduced in 2020 to refer to fatty liver disease associated with systemic metabolic dysregulation. The name change from nonalcoholic fatty liver disease (NAFLD) to fatty liver disease associated with metabolic dysfunction (MAFLD) was proposed to focus on the bidirectional interaction between fatty liver disease and metabolic changes and to emphasize the need to evaluate fatty liver disease independently of alcohol consumption and other comorbid causes of liver disease. Fatty liver disease associated with metabolic dysfunction (MAFLD) affects approximately 25% of the general population and more than 50% of patients with metabolic disorders. This new concept of MAFLD may have a broad impact on patients, physicians, healthcare professionals, and various stakeholders regarding fatty liver disease. In this way, MAFLD may influence clinical practice and increase awareness regarding fatty liver disease. This paper identifies differences between the MAFLD and NAFLD diagnoses, areas of benefit, potential limitations, and how the MAFLD terminology has opened up new areas of research.